Critical Time for Weed Removal in Dicamba tolerant Soybean as influenced by PRE emergence herbicides - Jovanović, Darko; Cuvaca, Ivan; Scott, Jon; Knezevic, Stevan (Acta herbologica, 2020)
Field experiment was conducted in 2019 at Haskell Agriculture Laboratory, Concord, NE, USA. Goal of the study was to test the influence of PRE-EM herbicides on the Critical Time for Weed Removal (CTWR) in dicamba tolerant soybean. The study was arranged in a split-plot design that consisted four herbicide regimes as main plot treatments and seven weed removal timings as subplot treatments with four replications. The herbicide regimes included: no PRE and glyphosate, acetochlor and dicamba as PRE and glyphosate as POST, acetochlor and dicamba as PRE and glyphosate and dicamba as POST, and acetochlor and fomesafen as PRE and acetochlor, glyphosate and dicamba as POST. The five weed removal times included the V1, V3, V6, R2 and R5, and there were also weedy and weed-free season long plots. By utilizing herbicide regimes, the CTWR was delayed to 632 GDD (until V4 soybean growth stage, 28 days after emergence) for acetochlor and dicamba as PRE and glyphosate as POST, 861 GDD (until V6 soybean growth stage, 32 days after emergence) for acetochlor and dicamba as PRE and glyphosate and dicamba as POST, and 1060 GDD (until R1 soybean growth stage, 42 days after emergence) for acetochlor and fomesafen as PRE and acetochlor, glyphosate and dicamba as POST.